Process optimization of glucoamylase production by aspergillus niger using low cost bitter cassava (manihot esculenta) - Alam, Md Zahangir; Khalaf, Abubakir I.; Mohd. Salleh, Hamzah; Salihu, Aliyu (AENSI Publications, 2014)
The effect of process parameters on glucoamylase production from bitter cassava by Aspergillus niger was studied using response surface methodology (RSM). Face centered central composite design (FCCCD) was selected to evaluate the optimum levels of the three parameters (pH, inoculum concentration and agitation speed) and the developed quadratic model was found to be significant with p-value < 0.0001. The most important parameter was pH based on its lowest p-value of < 0.0001 and the optimal combinations of the selected parameters for maximum glucoamylase production were found to be 4.8, 3.7% (v/v) and 260 rpm for pH, inoculum concentration and agitation speed respectively. The model R2 value of 0.9905 showed the fitness of the experimental response with the predicted ones. Thus, this study develops an efficient fermentation system using bitter cassava for enhanced production of glucoamylase production by A. nige